Prophetic Leadership: Examining The Prophetic Leadership Concept of The Prophet Muhammad SAW - Tiarani Mirela; Zainal Arifin; M. Jamroh; Kaspul Anwar Us (INNOVATIO: Journal for Religious Innovation Studies, 2021)
Abstract: In the study of Islamic Education Management (MPI), it is necessary to develop a theory or concept of leadership based on Islamic values, one of which is the concept of prophetic leadership. This study aims to analyze how the prophetic leadership concept of the Prophet Muhammad SAW can be applied in organizations. This research was conducted qualitatively with a literature review. Data analysis used the Miles and Huberman model, which consisted of three activities: data analysis, data reduction, and verification. The study results explain that the concept of prophetic leadership is leadership based on prophetic (apostolic) values. The prophetic leadership character of the Prophet Muhammad is known by four characters, namely Fatanah, Amanah, Sidiq, and Tabligh. Apart from these four characters, The Prophet Muhammad SAW is also known as a prophet whom Allah SWT sent to be a mercy for the universe. The implication of the Prophet Muhammad's Prophetic Leadership is that each of his followers is encouraged to imitate these characters and apply them in their daily lives. Abstrak: Dalam kajian Manajemen Pendidikan Islam (MPI) perlu mengembangkan teori atau konsep kepemimpinan yang berlandaskan pada nilai-nilai Islam, salah satunya adalah konsep kepemimpinan profetik. Tujuan penelitian ini untuk menganalisis bagaimana konsep kepemimpinan profetik Nabi Muhammad saw yang dapat diterapkan dalam organisasi. Penelitian ini dilakukan secara kualitatif dengan kajian literatur. Analisis data menggunakan model miles dan huberman yang terdiri dari tiga kegiatan, yaitu analisis data, reduksi data dan verifikasi. Hasil penelitian menjelaskan bahwa konsep kepemimpinan profetik adalah kepemimpinan yang didasarkan pada nilai-nilai kenabian (kerasulan). Karakter kepemimpinan profetik Nabi Muhammad saw, dikenal dengan empat karakter, yaitu Fatanah, Amanah, Shidiq, dan Tabligh. Selain empat karakter ini, Nabi Muhammad saw, juga dikenal sebagai nabi yang diutus oleh Allah swt untuk menjadi rahmat bagi semesta alam. Implikasi dari Kepemimpinan Profetik Nabi Muhammad saw adalah setiap umatnya didorong untuk meneladani karakter tersebut dan menerapkan dalam kehidupan sehari-hari. Kata-kata kunci: Kepemimpinan Profetik, Nabi Muhammad SAW, Rahmat